Geology at the Lower Secondary Educational Level (ISCED 2): Comparison of the Czech Republic, Estonia, Slovenia and Poland: Comparison of the Czech Republic, Estonia, Slovenia and Poland - Jedličková, Tereza; Svobodová, Andrea; Kachlík, Václav (Scientia in educatione, 2019)
Geology is a science with a highly interdisciplinary character. Thus, in education it is ideal to provide education in a form integrated with the other branches of natural sciences under the subject of Science or Natural Sciences. However, most European countries prefer separate teaching of the individual educational fields and subsume geology within one of them, most frequently biology or geography. The submitted study discusses the potential advantages and disadvantages of various strategies of allocation of geological topics in education. A comparative method is used to evaluate and analyse curricular documents in the Czech Republic, Estonia, Slovenia and Poland at the lower secondary educational level. The comparison is focused on the scope and incorporation of selected educational content of geology into individual educational subjects, and on the recommended teaching methods suitable for interpreting geological subject matter. On the basis of this knowledge from abroad, individual subjects are selected for the “best practice” and subsequently proposed for implementation under the conditions in the Czech Republic. This seeks to make geology more familiar and attractive for students at the lower secondary level of education.